Ascorbic acid protects retinal pigment epithelial cells from high glucose by inhibiting the NF‐κB signal pathway through MALAT1/IGF2BP3 axis. Issue 5 (7th February 2023) - Tian, Yanming; Cheng, Wubo; Wang, Haiyan; Zeng, Chengcheng; Chen, Xueyi
Abstract: Background: Diabetic retinopathy (DR) is a common complication of diabetes with nocuous effects on patients' eye health, typically accompanies by excessive inflammation and oxidative stress. Insulin‐like growth factor‐2 messenger RNA‐binding protein 3 (IGF2BP3) was engaged with inflammation, whereas its precise role in the DR process was unclear. And enhanced lncRNA metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) and decreased ascorbic acid (AA) were also found in DR. This study was to explore the regulatory role and mechanism of IGF2BP3, MALAT1 and AA in the high glucose (HG)‐induced retinal pigment epithelial (RPE) cell injury. Methods: ARPE‐19 cells were treated with HG to establish the in vitro RPE cell injury model. The mRNA and protein levels of the gene were evaluated by qRT‐PCR or Western blot. Immunofluorescence detected the translocation condition of the p65 protein. Inflammatory factor levels were detected by ELISA assays. Apoptosis was detected by flow cytometry. The binding interaction of IGF2BP3 and MALAT1 was validated by RIP‐qPCR assays. Results: In HG‐induced RPE cell injury, IGF2BP3 expression, inflammatory response and apoptosis were enhanced. Next, the IGF2BP3 activated the NF‐κB signalling to promote the RPE cell injury development. MALAT1 could directly bind with IGF2BP3 and up‐regulate its expression. In addition, AA ameliorated the HG‐induced RPE cell injury through the regulation of MALAT1. Conclusion: Ascorbic acid ameliorated HG‐induced RPE cell injury by repressing the NF‐κB signalling pathway via modulating the MALAT1/IGF2BP3 axis.